Examining the Role of Low Self-Control and Psychopathy in Explaining Poly-Victimization - Kulig, Teresa C. (Victims & offenders, 2024)
Although there has been research on the correlates of poly-victimization, studies have not fully considered the role of personality as a potential risk factor. The current study sought to address this gap by examining the personality characteristics of low self-control and psychopathy to assess how individuals who experience poly-victimization, defined as two or more different types of victimization, differ from non-victims and victims of only a single crime type. The sample was comprised of 872 undergraduate students at a southern university in the United States. Notably, 31.1% of victims experienced poly-victimization, including property, physical, or sexual harms. Consistent with prior work, lifestyle risk in the form of criminal behavior and adverse childhood experiences were associated with greater odds of poly-victimization. In addition, self-control proved to be a relatively robust correlate of poly-victimization. Psychopathy – measured as an aggregate measure and by separate subscale factors – was not associated with risk for poly-victimization. In this way, some subscales of personality traits such as low self-control seem to be important for explaining why some individuals experience poly-victimization. The findings provide preliminary evidence for personality traits as an important consideration in distinguishing poly-victimization from single- and non-victimization experiences in addition to other theoretically relevant factors.